Predicting Metastatic Potential in Pheochromocytoma and Paraganglioma: A Comparison of PASS and GAPP Scoring Systems - Wachtel, Heather (J Clin Endocrinol Metab, 2020)
PURPOSE: The Pheochromocytoma of the Adrenal Gland Scaled Score (PASS) and the Grading System for Adrenal Pheochromocytoma and Paraganglioma (GAPP) are scoring systems to predict metastatic potential in pheochromocytomas (PCC) and paragangliomas (PGLs). The goal of this study is to assess PASS and GAPP as metastatic predictors and to correlate with survival outcomes. METHODS: The cohort included PCC/PGL with ≥5 years of follow-up or known metastases. Surgical pathology slides were rereviewed. PASS and GAPP scores were assigned. Univariable and multivariable logistic regression, Kaplan–Meier survival analysis, and Cox proportional hazards were performed to assess recurrence-free survival (RFS) and disease-specific survival (DSS). RESULTS: From 143 subjects, 106 tumors were PCC and 37 were PGL. Metastases developed in 24%. The median PASS score was 6.5 (interquartile range [IQR]: 4.0-8.0) and median GAPP score was 3.0 (IQR: 2.0-4.0). Interrater reliability was low–moderate for PASS (intraclass correlation coefficient [ICC]: 0.6082) and good for GAPP (ICC 0.7921). Older age (OR: 0.969, P = .0170) was associated with longer RFS. SDHB germline pathogenic variant (OR: 8.205, P = .0049), extra-adrenal tumor (OR: 6.357, P < .0001), Ki-67 index 1% to 3% (OR: 4.810, P = .0477), and higher GAPP score (OR: 1.537, P = .0047) were associated with shorter RFS. PASS score was not associated with RFS (P = .1779). On Cox regression, a GAPP score in the moderately differentiated range was significantly associated with disease recurrence (HR: 3.367, P = .0184) compared with well-differentiated score. CONCLUSION: Higher GAPP scores were associated with aggressive PCC/PGL. PASS score was not associated with metastases and demonstrated significant interobserver variability. Scoring systems for predicting metastatic PCC/PGL may be improved by incorporation of histopathology, clinical data, and germline and somatic tumor markers.